Rapid screening for behavioral risk factors in adolescents in North India - Banga, Poonam; Singh, Tarundeep; Kumar, Rajesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Habits get established during the transitional age of adolescence making it important to conduct surveillance to detect high risk behaviours at an early age. Feasibility of such a surveillance system was tested for monitoring the risk factors in schools. Methods: A cross sectional survey was conducted in randomly selected schools of Chandigarh in India, by enrolling 226 students of class V to XII. A pretested structured questionnaire on dietary pattern, physical activity, tobacco and alcohol consumption, drug abuse, mental health, sexual behaviour etc., was administered after ensuring privacy and confidentiality. Results: A total of 226 students with a mean age of 14years (range 10 to 19years) participated in the study. The prevalence of tobacco use was 8%, alcohol consumption was 3%, and drug abuse was 4%. About 47% were involved in a physical fight. Around 7% students were overweight. About 50% of the students skipped breakfast during previous week, and 6% had no intake of fruits and vegetables in last one month. Only 53% reported consistent use of seat belts. Conclusions: Several behavioral risk factors were prevalent among school children in Chandigarh. Behaviour surveillance to monitor trends should be conducted at regular intervals.